Pistol Packin' Mama: Aunt Molly Jackson and the Politics of Folksong - Narvéez, Peter (Labour / Le Travail, 1999)
The article reviews the book, "Pistol Packin' Mama: Aunt Molly Jackson and the Politics of Folksong," by Shelly Romalis.